Treatment of a Tuberculous Empyema with Simultaneous Oral and Intrapleural Antituberculosis Drugs. Issue 5 (2008) - Long, Richard; Barrie, James; Stewart, Kenneth; Peloquin, Charles A
Abstract : A 71-year-old man was diagnosed with an uncomplicated tuberculous (TB) empyema. Differential penetration of anti-TB drugs, believed to explain the phenomenon of acquired drug resistance in TB empyema, was confirmed by measurement of serum and pleural fluid anti-TB drug concentrations. Simultaneous oral and intrapleural anti-TB drugs were administered and a cure was achieved. The present case is discussed in the context of the literature on acquired drug resistance in TB empyema. It is argued that high-end doses of oral drugs or combined oral plus intrapleural drugs, along with tube thoracostomy or intermittent thoracentesis, will cure uncomplicated TB empyema without threatening to induce drug resistance or having to resort to surgery.